Synthesis of chiral malonates by α-alkylation of 2,2-diphenylethyl tert-butyl malonates via enantioselective phase-transfer catalysis - Guo, Zhibin; Oh, Daehyun; Sagong, Min; Yang, Jewon; Lee, Geumwoo; Park, Hyeung-geun (Frontiers in Chemistry, 2023)
An efficient synthetic approach for chiral malonates was established via enantioselective phase transfer catalysis. The α-alkylation of 2,2-diphenylethyl tert-butyl α-methylmalonates with (S,S)-3,4,5-trifluorophenyl-NAS bromide as a phase-transfer catalyst under phase-transfer catalytic conditions successfully produced corresponding α-methyl-α-alkylmalonates; these compounds are versatile chiral building blocks containing a quaternary carbon center in high chemical yields (up to 99%) with excellent enantioselectivities (up to 98% ee). α,α-Dialkylmalonates were selectively hydrolyzed to the corresponding chiral malonic monoacids under basic (KOH/MeOH) and acidic conditions (TFA/CH2Cl2), showing the practicality of the method.